EXPLORING DISCOURSE MARKERS IN COMPLAINTS: A COMPARATIVE ANALYSIS OF NATIVE AND NON-NATIVE ITALIAN SPEAKERS (Italiano LinguaDue, 2025)
This study aims to explore the use of discourse markers (DMs) in complaints by native and non-native speakers of Italian, focusing on how DMs are employed across different proficiency levels. The goal is to understand the role of DMs in mitigating, intensifying, or structuring complaints in Italian language learners at A1-A2 and B1-B2 levels compared to native speakers. The data were collected through written discourse completion tasks (DCTs), which elicited participants’ responses in various complaint scenarios. The quantitative analysis revealed distinct patterns in DM usage among the three groups, with A1-A2 learners displaying a higher frequency but narrower variety of DMs compared to more advanced learners and native speakers. The DMs used by lower-level learners were mainly interactional, serving to seek attention and employ basic politeness strategies. At the B1-B2 level, a broader range of DMs was observed, fulfilling functions such as mitigating or reinforcing the complaint, modulating certainty, and managing the expressive tone of the interaction. Native speakers showed the most structured complaints and utilized a diverse array of DMs to balance the illocutionary force of their complaints. A consistent finding across all groups was the prevalent use of the dyad scusa/scusi ma highlighting its function in introducing criticism and expressing contrasts in complaint scenarios. Esplorare i marcatori del discorso nelle proteste: un’analisi comparativa di parlanti nativi e non nativi italianiQuesto studio si propone di esplorare l’uso dei segnali discorsivi (SD) nelle proteste di parlanti nativi e non nativi di italiano, concentrandosi su come vengano impiegati nei diversi livelli di competenza. L’obiettivo è comprendere il ruolo dei SD nell’attenuare, intensificare o strutturare le proteste tra apprendenti di italiano ai livelli A1-A2 e B1-B2 rispetto ai parlanti nativi. I dati sono stati raccolti attraverso DCT scritti, che hanno sollecitato risposte in diversi scenari. L’analisi quantitativa ha rivelato distinti patterns nell’uso dei SD tra i tre gruppi: gli apprendenti A1-A2 mostrano una frequenza maggiore ma una varietà minore rispetto a quelli più avanzati e ai parlanti nativi. I segnali utilizzati dai principianti erano prevalentemente interazionali, volti a richiamare l’attenzione e a impiegare strategie di cortesia molto semplici. Al livello B1-B2 si osserva una gamma più ampia di SD, che servono a mitigare o rinforzare la protesta, modulare la certezza e gestire il tono espressivo dell’interazione. I parlanti nativi presentano atti più strutturati e utilizzano una varietà diversificata di SD per bilanciare la forza illocutiva delle loro proteste. Un risultato comune a tutti i gruppi è l’uso prevalente della diade scusa/scusi ma, che evidenzia la sua funzione nell’introdurre critiche ed esprimere contrasti nei diversi scenari esaminati.